Effects of physically active maths lessons on children’s maths performance and maths-related affective factors: Multi-arm cluster randomized controlled trial - Syväoja, Heidi Johanna (John Wiley & Sons Ltd., 2025)
Background: Physical activity (PA) may benefit academic performance, but it is unclear what kind of classroom-based PA is optimal for learning.
Aim: We studied the effects of physically active maths les- sons on children's maths performance and maths-related effects, and whether gender and previous mathematical or motor skills modify these effects.
Sample: A total of 22 volunteered teachers and their pu- pils with signed consent (N=397, mean age: 9.3years, 51% females) participated in a 5-month, teacher-led, multi-arm, cluster-randomized controlled trial.
Methods: The intervention included a PAL group (20min of physically active learning in each 45-min lesson), a breaks group (two 5-min PA breaks in each 45-min les- son) and a control group (traditional teaching). Maths performance was assessed with a tailored curriculum- based test. Maths-related enjoyment, self-perceptions and anxiety were measured with a self-reported questionnaire. The individual-level intervention effects were tested via covariate-adjusted linear mixed-effect models with school classes serving as random effects.
Results: Changes in maths performance or self-perceptions did not differ between the intervention groups. Maths anxi- ety in learning situations increased in the PAL group (effect .28, 95% CI=.01–.56); there was no change in the other groups. Subgroup analyses suggested that maths anxiety in- creased in the PAL group among children in the two lowest tertiles of motor skills. It decreased in the highest tertile. Enjoyment decreased in the breaks group among pupils in the lowest motor skill tertile.
Conclusions: Physically active maths lessons did not affect maths performance or self-perceptions but had divergent ef- fects on maths anxiety and enjoyment, depending on motor skills.